2016
DOI: 10.18632/oncotarget.8169
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 is an independent prognostic predictor in gastric cancer of Western patients

Abstract: Targeting the PD-1/PD-L1 immune checkpoint signaling is a novel promising treatment strategy in several tumor entities, and it is suggested that PD-L1/PD-1 expression is predictive for a PD-1/PD-L1 checkpoint inhibitor treatment response. We investigated the expression of PD-L1 and PD-1 by immunohistochemistry in a large and well characterized gastric cancer (GC) cohort of Caucasian patients, consisting of 465 GC samples and 15 corresponding liver metastases. Staining results were correlated with clinico-patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
265
5
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(319 citation statements)
references
References 30 publications
20
265
5
19
Order By: Relevance
“…Several studies have demonstrated that PD-L1 immunoexpression is heterogeneous in GC, as in other tumour models. PD-L1 overexpression is associated with high densities of CD3+ and CD8+ tumour-infiltrating lymphocytes [67][68][69], GC with lymphoid stroma morphology [70], and both an EBV+ and MSI-high molecular status [69,[71][72][73][74]. However, the correlation with PD-L1 amplification, prognosis, and response to targeted immunotherapies is still debated and deserves further study.…”
Section: Moving Towards Molecular Subtyping and Precision Medicinementioning
confidence: 99%
“…Several studies have demonstrated that PD-L1 immunoexpression is heterogeneous in GC, as in other tumour models. PD-L1 overexpression is associated with high densities of CD3+ and CD8+ tumour-infiltrating lymphocytes [67][68][69], GC with lymphoid stroma morphology [70], and both an EBV+ and MSI-high molecular status [69,[71][72][73][74]. However, the correlation with PD-L1 amplification, prognosis, and response to targeted immunotherapies is still debated and deserves further study.…”
Section: Moving Towards Molecular Subtyping and Precision Medicinementioning
confidence: 99%
“…PD-L1 has been detected in the tumor microenvironment of GCs including tumor cells, stromal and immune cells. The largest gastro-esophageal cancer cohort reported, to date, examined PD-L1 expression in 465 German gastric/gastro-esophageal junction (GEJ) cancer cases by immunohistochemistry (IHC) (antibody E1L3N clone, Cell Signaling) (27). The following expression patterns were found:…”
Section: Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
“…In both studies, PD-L1 tumor-cell positivity had an association with favorable overall survival that was either statistically significantly (27) or trended toward significance (28). However, other investigations in gastro-esophageal cancer have reported an adverse association between PD-L1 expression and survival (30)(31)(32)(33)35,36).…”
Section: Pd-l1 Expression In Gastro-esophageal Tumorsmentioning
confidence: 99%
“…A molecular classification was proposed, which categorizes four subtypes, i.e., Epstein–Barr-virus-associated (EBVa), microsatellite instable (MSI), chromosomal instable (CIN) and genomically stable (GS) GCs 2 , 3 . Two of the four molecular subtypes, EBVa and MSI GC, are significantly associated with an increased PD-L1 expression and are thereby suggested to be particular suitable for an immune checkpoint therapy 4 . Moreover, MSI GCs are characterized by a high-mutational load, which is associated with a better response to anti-PD-1/PD-L1 immune checkpoint therapies in several tumor entities 5 .…”
Section: Introductionmentioning
confidence: 99%